Bi-crosslinking antibacterial hydrogel flexible sensing material based on sodium alginate as well as preparation method and application of bi-crosslinking antibacterial hydrogel flexible sensing material
Through modification processes and ionic crosslinking technology, a dual crosslinking antibacterial hydrogel flexible sensing material based on sodium alginate was prepared, which solved the challenges of existing materials in terms of mechanical properties, flexibility and biocompatibility, achieved high performance and low cost production of materials, and enhanced the application potential of wearable devices.
Patent Information
- Application Number
- CN202510315281.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-06-27
AI Technical Summary
The application of existing sodium alginate-based hydrogel materials in human wearable devices faces challenges in mechanical properties, flexibility, biocompatibility and production processes, and additives may bring biotoxicity or skin irritation, reducing biocompatibility and safety.
Through modification process and ionic crosslinking technology, a dual crosslinking antibacterial hydrogel flexible sensing material based on sodium alginate was prepared. Materials such as aldehyde-based sodium alginate, acrylic acid and silver-based carbon nanotubes were used to form a three-dimensional network structure and crosslink it through calcium ion to enhance the mechanical properties and biocompatibility of the material.
The good mechanical properties, flexibility, biocompatibility, stability, self-healing and antibacterial properties of the material are achieved, which reduces production costs and improves the safety and industrialization prospects of the material.
Smart Images

Figure CN120209365A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sodium alginate hydrogel composite material, specifically a double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate, and its preparation method and application. Background Art
[0002] Sodium alginate is a natural polysaccharide extracted from seaweed and has been widely used in the fields of food, medicine, and biomaterials. Due to its good biocompatibility, biodegradability, and gel-forming ability, it has attracted increasing attention from researchers in the medical and environmental protection fields. However, the application of existing sodium alginate-based hydrogel materials in human wearable devices still faces a series of challenges.
[0003] On the one hand, although existing sodium alginate-based gel materials have certain flexibility, they are prone to breakage or deformation in a complex mechanical environment, limiting their stability for long-term wear. On the other hand, the stability and function tunability of these materials in a physiological environment are poor, making it difficult to meet the application requirements of diverse wearable devices. Moreover, the preparation process of existing human wearable gel materials is relatively complex and the production cost is high, severely restricting their large-scale application. In addition, in order to improve the performance of human wearable gel materials, additives are often required, which brings biological toxicity or skin irritation and reduces their biocompatibility and safety.
[0004] Therefore, there is an urgent need to develop a fully sodium alginate-based wearable sensor hydrogel material to solve the technical problems existing in the mechanical properties, flexibility, biocompatibility, and production process of traditional materials, so as to achieve the improvement of material functions and the control of production costs. Summary of the Invention
[0005] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate, and its preparation method and application. Through a simple modification process and ion crosslinking technology, a hydrogel with good mechanical properties, flexibility, biocompatibility, stability, self-healing property, and sensing performance is prepared.
[0006] To achieve the above purpose, the present invention adopts the following technical solutions to be realized:
[0007] A preparation method of a double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate, comprising the following steps:
[0008] Step 1: By mass fraction, place 0.1 - 1 part of carbon nanotubes in a mixed solution of 50 - 100 parts of sulfuric acid and nitric acid. Heat under reflux at 70 - 80 °C for 4 - 4.5 h, and wash to remove impurities to obtain acidified carbon nanotubes. Place the acidified carbon nanotubes in 50 - 100 parts of a 1.5% silver ammonia solution, stir for 2 - 3 h, perform centrifugal separation and vacuum drying to obtain silver-based carbon nanotubes;
[0009] Step 2: By mass fraction, dissolve 0.1 - 1 part of sodium alginate in 100 - 200 parts of deionized water to obtain a sodium alginate solution. Add 0.1 - 1 part of sodium periodate to the sodium alginate solution, stir at room temperature for 2 - 6 h, perform vacuum filtration and vacuum drying to obtain solid aldehyde-functionalized sodium alginate;
[0010] Step 3: By mass fraction, mix 0.1 - 1 part of aldehyde-functionalized sodium alginate, 1 - 5 parts of acrylic acid, 20 - 100 parts of deionized water and 0.01 - 0.05 part of N,N'-methylenebisacrylamide, stir evenly, add 0.01 - 0.1 part of silver-based carbon nanotubes, perform ultrasonic dispersion for 20 - 30 min, then add 0.01 - 0.1 part of ammonium persulfate, and irradiate under ultraviolet light for 4 - 4.5 h to carry out a cross-linking reaction to obtain a modified sodium alginate / acrylic acid resin / silver-based carbon nanotube single-network hydrogel precursor;
[0011] Step 4: Immerse 21 - 106 parts of the modified sodium alginate / acrylic acid resin / silver-based carbon nanotube single-network hydrogel precursor in 200 - 300 parts of a 5% calcium chloride solution for 2 - 3 h to obtain a flexible sensing material of a double-crosslinked antibacterial hydrogel based on sodium alginate.
[0012] Further, the carbon nanotubes in Step 1 are single-walled carbon nanotubes with a purity of 95%, an outer wall diameter of 1 - 2 nm, and a length of 4 - 20 μm.
[0013] Further, the mixed solution of sulfuric acid and nitric acid is composed of a 98% sulfuric acid solution and a 69.8% nitric acid solution, mixed in a volume ratio of 2:1.
[0014] Further, the washing in Step 1 is carried out 3 times with deionized water.
[0015] Further, the silver ammonia solution in Step 1 is prepared by the following method: Take 30 mL of a 2% silver nitrate solution, and gradually add dropwise a 2% dilute ammonia water to it until the precipitate just disappears to obtain a clear and transparent solution, which is a 1.5% silver ammonia solution.
[0016] Further, the temperature of the vacuum drying in Step 1 and Step 2 is 50 - 60 °C.
[0017] Further, the sodium alginate in step 2 has a molecular weight of 50,000 to 200,000, and the viscosity of the sodium alginate solution is 850 to 1000 mPa·s.
[0018] Further, the purities of sodium periodate, acrylic acid, and N,N - methylenebisacrylamide are all 99.5%.
[0019] A double - crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate.
[0020] Application of a double - crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate as a sensing material in flexible wearable devices, medical devices, and human - machine interaction interfaces.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] 1), The double - crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate prepared by the present invention has good mechanical properties, flexibility, and stretchability: Using silver - based carbon nanotubes (Ag - CNTs) as fillers, aldehyde - modified sodium alginate (OSA) and acrylic acid (AA) as the hydrogel matrix, and N,N - methylenebisacrylamide (MBA) as the cross - linker, a hydrogel precursor with a three - dimensional network structure formed by intermolecular forces, hydrogen bonds, and ionic bonds among modified sodium alginate / acrylic acid resin / silver - based carbon nanotubes is prepared. Immerse it in a calcium chloride solution, and calcium ions form a new cross - linked network with the carboxyl groups in the already formed three - dimensional network structure, thereby enhancing the mechanical strength of the hydrogel. There is a double - crosslinked network structure in the prepared hydrogel, improving the stability and mechanical properties of the gel, and endowing it with good stretchability and toughness.
[0023] 2), The sodium alginate - based double - crosslinked antibacterial hydrogel flexible sensing material prepared by the present invention has good biocompatibility and stability: Sodium alginate itself has good biocompatibility. At the same time, the introduced Ag - CNTs not only help to improve the antibacterial performance of the material but also can further enhance the biocompatibility of the material. In addition, the cross - linking of sodium alginate and acrylic acid enhances the stability.
[0024] 3), The sodium alginate - based double - crosslinked antibacterial hydrogel flexible sensing material prepared by the present invention has good self - healing properties: It contains dynamic covalent bonds, such as the C=N bond in MBA, and hydrogen bonds. The dynamic covalent bonds allow polymer chains to rearrange and re - establish connections after damage, and the polymer network of the gel also supports this self - healing ability, enabling the material to recover after mechanical stress and continue to function.
[0025] 4) The alginate-based double-crosslinked antibacterial hydrogel flexible sensing material prepared by the present invention has good antibacterial properties: the incorporation of Ag-CNTs significantly improves the antibacterial performance of the hydrogel, which is attributed to the interaction between silver nanoparticles (AgNPs) on carbon nanotubes (CNTs) and the bacterial cell wall, destroying the structure and function of the bacterial cell wall, thereby inhibiting bacterial growth. Moreover, the acidic environment generated by acrylic acid can also inhibit the growth of bacteria. Therefore, the gel material synthesized by the present invention has good antibacterial effects on both Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus).
[0026] 5) The alginate-based double-crosslinked antibacterial hydrogel flexible sensing material prepared by the present invention has good adhesion to human skin: the natural properties of alginate endow the gel with good adhesion, enabling it to adhere to various surfaces, including human skin. In addition, the combination of hydrogen bonds, electrostatic interactions, and van der Waals forces also promotes this self-adhesion.
[0027] 6) By a simple, environmentally friendly, and low-cost method, the alginate-based double-crosslinked antibacterial hydrogel flexible sensing material prepared by the present invention has good mechanical properties, flexibility, stretchability, biocompatibility, stability, self-healing property, antibacterial property, and self-adhesion. It can be used as a conductive and sensing material for long-term flexible wearable devices, medical devices, and human-computer interaction interfaces. Moreover, the preparation method is simple, environmentally friendly, and low-cost, and has good industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the synthesis process of the silver-based carbon nanotubes of the present invention;
[0029] Figure 2 is the infrared spectrogram of carbon nanotubes, acidified carbon nanotubes, and silver-based carbon nanotubes during the synthesis of the silver-based carbon nanotubes of the present invention;
[0030] Figure 3 is the physical photo of carbon nanotubes, acidified carbon nanotubes, and silver-based carbon nanotubes during the synthesis of the silver-based carbon nanotubes of the present invention;
[0031] Figure 4 is the synthesis process of the alginate-based double-crosslinked antibacterial hydrogel flexible sensing material of the present invention;
[0032] Figure 5 is the physical picture of the original state and different stretching states of the alginate-based double-crosslinked antibacterial hydrogel flexible sensing material of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0033] The following further elaborates and explains the specific content of the present invention in detail in conjunction with embodiments.
[0034] In Examples 1 to 5 of the present invention, the sulfuric acid and nitric acid mixed solution selected is composed of a sulfuric acid solution with a mass fraction of 98% and a nitric acid solution with a mass fraction of 69.8%, and they are mixed according to a volume ratio of 2:1.
[0035] In Examples 1 to 5 of the present invention, the carbon nanotubes selected are single-walled carbon nanotubes with a purity of 95%, an outer wall diameter of 1 - 2 nm, and a length of 4 - 20 μm.
[0036] In Examples 1 to 5 of the present invention, the purities of sodium periodate, acrylic acid, and N,N'-methylenebisacrylamide are all 99.5%.
[0037] In Examples 1 to 5 of the present invention, the molecular weight of sodium alginate selected is 50,000 - 200,000, and the viscosity of the prepared sodium alginate solution is 850 - 1000 mPa·s.
[0038] In Examples 1 to 5 of the present invention, the preparation process of the silver ammonia solution used is as follows: Dropwise add a 2% dilute ammonia water to 30 mL of a 2% silver nitrate solution until the generated precipitate just disappears to obtain a clear and transparent solution, which is a 1.5% silver ammonia solution.
[0039] Example 1
[0040] Step 1: By mass, place 0.1 part of carbon nanotubes into 50 parts of the sulfuric acid and nitric acid mixed solution, reflux and heat at 70 °C for 4 h to obtain acidified carbon nanotubes. Wash them 3 times with deionized water to remove impurities, then place the acidified carbon nanotubes into 50 parts of a 1.5% silver ammonia solution, stir and react for 2 h, and use a high-speed centrifuge to centrifuge and separate the solid matter, and vacuum dry at 50 °C to obtain powdery silver-based carbon nanotubes;
[0041] Step 2: By mass, dissolve 0.1 part of sodium alginate in 100 parts of deionized water to obtain a sodium alginate solution. Add 0.1 part of sodium periodate to the sodium alginate solution, stir at room temperature for 2 h, vacuum filter, and vacuum dry at 50 °C to obtain solid aldehyde-functionalized sodium alginate;
[0042] Step 3: By mass, mix 0.1 part of aldehyde-functionalized sodium alginate, 1 part of acrylic acid, 20 parts of deionized water, and 0.01 part of N,N'-methylenebisacrylamide, stir evenly, add 0.01 part of silver-based carbon nanotubes, perform ultrasonic dispersion for 20 min, then add 0.01 part of ammonium persulfate, and irradiate with ultraviolet light for 4 h to carry out a crosslinking reaction to form a modified sodium alginate / acrylic acid resin / silver-based carbon nanotube single-network hydrogel precursor;
[0043] Step 4: Soak 21 parts by mass of the hydrogel precursor obtained in Step 3 in 200 parts of a 5% calcium chloride solution by mass for 2 h to obtain a double-crosslinked antibacterial hydrogel flexible sensing material of sodium alginate.
[0044] Example 2
[0045] Step 1: Place 0.3 parts by mass of carbon nanotubes in a mixed solution of 70 parts of sulfuric acid and nitric acid, reflux and heat at 75 °C for 4.5 h to obtain acidified carbon nanotubes. Wash with deionized water 3 times to remove impurities. Then place the acidified carbon nanotubes in 70 parts of a 1.5% silver ammonia solution by mass, stir and react for 2.5 h, and use a high-speed centrifuge to centrifuge and separate the solid matter. Vacuum dry at 55 °C to obtain silver-based carbon nanotubes;
[0046] Step 2: Dissolve 0.3 parts by mass of sodium alginate in 120 parts of deionized water to obtain a sodium alginate solution. Add 0.3 parts by mass of sodium periodate to the sodium alginate solution, stir at room temperature for 3 h, vacuum filter, and vacuum dry at 55 °C to obtain aldehyde-group modified sodium alginate;
[0047] Step 3: Mix 0.3 parts by mass of aldehyde-group modified sodium alginate, 2.5 parts by mass of acrylic acid, 40 parts of deionized water, and 0.03 parts by mass of N,N'-methylenebisacrylamide, stir evenly, add 0.03 parts by mass of silver-based carbon nanotubes, perform ultrasonic dispersion for 25 min, then add 0.05 parts by mass of ammonium persulfate, and irradiate with ultraviolet light for 4.5 h to carry out a crosslinking reaction to form a modified sodium alginate / acrylic acid resin / silver-based carbon nanotube single-network hydrogel precursor;
[0048] Step 4: Soak 43 parts by mass of the hydrogel precursor obtained in Step 3 in 250 parts of a 5% calcium chloride solution by mass for 2 h to obtain a double-crosslinked antibacterial hydrogel flexible sensing material of sodium alginate.
[0049] Example 3
[0050] Step 1: Place 0.5 parts by mass of carbon nanotubes in a mixed solution of 80 parts of sulfuric acid and nitric acid, reflux and heat at 80 °C for 4 h to obtain acidified carbon nanotubes. Wash with deionized water 3 times to remove impurities. Then place the acidified carbon nanotubes in 80 parts of a 1.5% silver ammonia solution by mass, stir for 2.5 h, and use a high-speed centrifuge to centrifuge and separate the solid matter. Vacuum dry at 60 °C to obtain silver-based carbon nanotubes;
[0051] Step 2: Dissolve 0.5 parts by mass of sodium alginate in 150 parts of deionized water to obtain a sodium alginate solution. Add 0.5 parts by mass of sodium periodate to the sodium alginate solution, stir at room temperature for 4 h, perform vacuum filtration, and vacuum dry at 60 °C to obtain solid aldehyde-functionalized sodium alginate;
[0052] Step 3: Mix 0.5 parts by mass of aldehyde-functionalized sodium alginate, 3 parts by mass of acrylic acid, 80 parts by mass of deionized water, and 0.03 parts by mass of N,N'-methylenebisacrylamide. After stirring evenly, add 0.5 parts by mass of silver-functionalized carbon nanotubes, perform ultrasonic dispersion for 30 min, then add 0.05 parts by mass of ammonium persulfate, and irradiate under ultraviolet light for 4 h to carry out a cross-linking reaction to form a modified sodium alginate / acrylic acid resin / silver-functionalized carbon nanotube single-network hydrogel precursor.
[0053] Step 4: Immerse 64 parts by mass of the hydrogel precursor obtained in Step 3 in 250 parts by mass of a 5% calcium chloride solution for 2.5 h to obtain a double-crosslinked antibacterial hydrogel flexible sensing material of sodium alginate.
[0054] Example 4
[0055] Step 1: Place 0.7 parts by mass of carbon nanotubes in a mixed solution of 70 parts by mass of sulfuric acid and nitric acid, reflux and heat at 70 °C for 4.5 h to obtain acidified carbon nanotubes. Wash with deionized water 3 times to remove impurities, then place the acidified carbon nanotubes in 60 parts by mass of a 1.5% silver ammonia solution, stir and react for 3 h, use a high-speed centrifuge to centrifuge and separate the solid, and vacuum dry at 60 °C to obtain silver-functionalized carbon nanotubes;
[0056] Step 2: Dissolve 0.7 parts by mass of sodium alginate in 170 parts of deionized water to obtain a sodium alginate solution. Add 0.7 parts by mass of sodium periodate to the sodium alginate solution, stir at room temperature for 6 h, perform vacuum filtration, and vacuum dry at 60 °C to obtain solid aldehyde-functionalized sodium alginate;
[0057] Step 3: Mix 0.8 parts by mass of aldehyde-functionalized sodium alginate, 4 parts by mass of acrylic acid, 80 parts by mass of deionized water, and 0.04 parts by mass of N,N'-methylenebisacrylamide. After stirring evenly, add 0.8 parts by mass of silver-functionalized carbon nanotubes, perform ultrasonic dispersion for 30 min, then add 0.04 parts by mass of ammonium persulfate, and irradiate under ultraviolet light for 4.5 h to carry out a cross-linking reaction to form a modified sodium alginate / acrylic acid resin / silver-functionalized carbon nanotube single-network hydrogel precursor;
[0058] Step 4: Immerse 86 parts by mass of the hydrogel precursor obtained in Step 3 in 300 parts by mass of a 5% calcium chloride solution for 2 h to obtain a double-crosslinked antibacterial hydrogel flexible sensing material of sodium alginate.
[0059] Example 5
[0060] Step 1: By mass, 1 part of carbon nanotubes is placed in a mixed solution of 100 parts of sulfuric acid and nitric acid, refluxed and heated at 80 °C for 4.5 h to obtain acidified carbon nanotubes. After washing 3 times with deionized water to remove impurities, the acidified carbon nanotubes are placed in 100 parts of a silver ammonia solution with a mass fraction of 1.5%, stirred and reacted for 3 h, and the solid is separated by high-speed centrifugation and vacuum dried at 60 °C to obtain silver-based carbon nanotubes;
[0061] Step 2: By mass, 1 part of sodium alginate is dissolved in 200 parts of deionized water to obtain a sodium alginate solution. 1 part of sodium periodate is added to the sodium alginate solution, stirred at room temperature for 6 h, vacuum filtered, and vacuum dried at 60 °C to obtain solid aldehyde-functionalized sodium alginate;
[0062] Step 3: By mass, 1 part of aldehyde-functionalized sodium alginate, 5 parts of acrylic acid, 100 parts of deionized water, and 0.05 part of N,N'-methylenebisacrylamide are mixed, stirred evenly, 0.1 part of silver-based carbon nanotubes is added, ultrasonic dispersion is carried out for 30 min, then 0.1 part of ammonium persulfate is added, and irradiated under ultraviolet light for 4.5 h for crosslinking reaction to form a modified sodium alginate / acrylic acid resin / silver-based carbon nanotube single-network hydrogel precursor;
[0063] Step 4: By mass, 107 parts of the hydrogel precursor obtained in Step 3 are immersed in 300 parts of a calcium chloride solution with a mass fraction of 5% for 3 h to obtain a double-crosslinked antibacterial hydrogel flexible sensing material of sodium alginate.
[0064] Comparative Example 1
[0065] Step 1: By mass, 0.3 part of sodium alginate is dissolved in 120 parts of deionized water to obtain a sodium alginate solution. 0.3 part of sodium periodate is added to the sodium alginate solution, stirred at room temperature for 3 h, vacuum filtered, and vacuum dried at 55 °C to obtain aldehyde-functionalized sodium alginate;
[0066] Step 2: By mass, 0.3 part of aldehyde-functionalized sodium alginate, 2.5 parts of acrylic acid, 40 parts of deionized water, and 0.03 part of N,N'-methylenebisacrylamide are mixed, stirred evenly, 0.05 part of ammonium persulfate is added, and irradiated under ultraviolet light for 4.5 h for crosslinking reaction to form a modified sodium alginate / acrylic acid resin single-network hydrogel precursor;
[0067] Step 3: By mass, 43 parts of the hydrogel precursor obtained in Step 3 are immersed in 250 parts of a calcium chloride solution with a mass fraction of 5% for 2 h to obtain a double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate.
[0068] Comparative Example 2
[0069] Step 1: Weigh 0.3 parts of sodium alginate and dissolve it in 120 parts of deionized water by mass to obtain a sodium alginate solution. Add 0.3 parts of sodium periodate to the sodium alginate solution, stir at room temperature for 3 h, perform vacuum filtration, and then conduct vacuum drying at 55 °C to obtain aldehyde-functionalized sodium alginate.
[0070] Step 2: Weigh 0.3 parts of aldehyde-functionalized sodium alginate, 2.5 parts of acrylic acid, 40 parts of deionized water, and 0.03 parts of N,N'-methylenebisacrylamide, mix them evenly, then add 0.05 parts of ammonium persulfate, and irradiate with ultraviolet light for 4.5 h to carry out a cross-linking reaction to obtain a modified sodium alginate / acrylic resin / single-network hydrogel.
[0071] The properties of the double-crosslinked antibacterial hydrogel flexible sensing materials based on sodium alginate prepared in Examples 1 to 5 and Comparative Example 1 and the modified sodium alginate / acrylic resin single-network hydrogel prepared in Comparative Example 2 were tested, and the results are shown in Table 1.
[0072] Table 1 Performance test results of the final products prepared in Examples 1 to 5 and Comparative Example 1
[0073]
[0074]
[0075] As can be seen from Table 1, the double-crosslinked antibacterial hydrogel flexible sensing materials based on sodium alginate prepared in Examples 1 to 5 have good mechanical strength and toughness as well as excellent electrical conductivity, which is attributed to the fact that a network structure is formed for the first time among sodium alginate / polyacrylic acid resin / silver-functionalized carbon nanotubes (Ag-CNTs) and a cross-linked network structure is formed for the second time between them and calcium ions in the prepared hydrogel. This double-crosslinked network structure enhances the mechanical strength and toughness of the hydrogel. The main role of Ag-CNTs is to improve the electrical conductivity. At the same time, due to the presence of active groups such as hydroxyl and carboxyl groups on the surface of the modified Ag-CNTs, while improving the electrical conductivity of the hydrogel, it also helps to improve its toughness and modulus.
[0076] To further verify the performance of the gel material prepared by the present invention, based on Example 2, Comparative Example 1 and Comparative Example 2 were designed. Among them: in Comparative Example 1, the conductive material silver-based carbon nanotubes were not incorporated; in Comparative Example 2, the process of not incorporating silver-based carbon nanotubes and not immersing in calcium chloride solution was carried out. In addition, as can be seen from Table 1, the maximum fracture strain, toughness and modulus of Comparative Example 1 were similar to those of Example 2, but its conductivity was only 0.08 mS / cm. This is because the silver-based carbon nanotubes with conductive functions were not added. The weak conductivity is due to the fact that there are still conductive groups and ions such as sodium ions, calcium ions and carboxyl groups in the hydrogel prepared in Comparative Example 1, and a weak conductivity can still be shown; the maximum fracture strain, toughness, modulus and conductivity of the gel prepared in Comparative Example 2 were significantly smaller than those of the gel prepared in the Example. The reason is that the silver-based carbon nanotubes with conductive functions were not incorporated and the secondary cross-linked structure was not formed by treatment with calcium chloride solution.
[0077] By analyzing the results in Table 1, it can be known that the present invention successfully achieved the balance of high modulus and high fracture strain of the gel material by ingeniously designing the double cross-linked system structure among sodium alginate - acrylic acid - calcium ions, enabling the material to have both good stretchability and toughness. In addition, Ag-CNTs formed an effective conductive network in the material, providing a good basis for the application of the material in flexible electronics, sensors and other fields.
[0078] It can be seen from Figure 1 that in Examples 1 to 5, the carbon nanotubes were acidified by a mixed solution of sulfuric acid and nitric acid, and functional groups such as carboxyl groups and hydroxyl groups were introduced on the surface of the carbon nanotubes to obtain acidified carbon nanotubes, which improved the dispersibility and reactivity of the carbon nanotubes. The acidified carbon nanotubes reacted with silver ions, and the silver ions were reduced to silver nanoparticles at the carboxyl groups of the carbon nanotubes to form silver-based carbon nanotubes Ag-CNTs.
[0079] It can be seen from Figure 2 that after acidifying the CNTs, -OH, -COOH and -C=O oxygen-containing functional groups were introduced on the surface of the CNTs. These functional groups significantly enhanced the dispersibility of the CNTs in water, improved their surface reactivity, facilitated the subsequent binding of silver ions, reduced the silver ions on the surface of the carbon nanotubes, and then formed silver nanoparticles to form silver-based carbon nanotubes Ag-CNTs, enhancing the antibacterial performance of the carbon nanotubes.
[0080] It can be seen from Figure 3 that the dispersibility of silver-based carbon nanotubes Ag-CNTs and acidified carbon nanotubes Acidized CNTs in water was significantly better than that of carbon nanotubes CNTs in water. At the same time, the dispersibility of silver-based carbon nanotubes Ag-CNTs in water was better.
[0081] From Figure 4 It can be seen that the present invention synthesizes a double-crosslinked antibacterial hydrogel flexible sensing material OSA-g-P(AA-co-MBA) / Ag-CNTs based on sodium alginate by a two-step method. In the first step, a single-network crosslinked hydrogel is prepared by ultraviolet light-induced polymerization. During this process, acrylic acid (AA) and N,N'-methylenebisacrylamide (MBA) are grafted onto oxidized algal polysaccharide (i.e., aldehyde-functionalized sodium alginate OSA) to form a single-network crosslinked structure OSA-g-p (i.e., AA-co-MBA). In the second step, the hydrogel is immersed in a calcium chloride solution to form a double-crosslinked hydrogel network, which has good mechanical properties, flexibility, self-healing property, stretchability and flexible sensing characteristics.
[0082] From Figure 5 It can be seen that the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate prepared in Example 1 has good toughness and stretchability.
Claims
1. A method for preparing a double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate, characterized in that: The steps include: Step 1, by weight, placing 0.1 to 1 parts of carbon nanotubes in 50 to 100 parts of a mixed solution of sulfuric acid and nitric acid, reflux heating at 70 to 80° C. for 4 to 4.5 hours, washing to remove impurities, and obtaining acidified carbon nanotubes, placing the acidified carbon nanotubes in 50 to 100 parts of a silver ammonia solution with a mass fraction of 1.5%, stirring for 2 to 3 hours, centrifugation, and vacuum drying to obtain powdered silver-based carbon nanotubes; Step 2, dissolving 0.1 to 1 part of sodium alginate in 100 to 200 parts of deionized water by mass to obtain a sodium alginate solution, adding 0.1 to 1 part of sodium periodate to the sodium alginate solution, stirring at room temperature, reacting for 2 to 6 hours, vacuum filtering, and vacuum drying to obtain solid aldehyded sodium alginate; Step 3, by weight, 0.1-1 parts of aldehyded sodium alginate, 1-5 parts of acrylic acid, 20-100 parts of deionized water and 0.01-0.05 parts of N,N'-methylenebisacrylamide are mixed, stirred evenly, 0.01-0.1 parts of silver-based carbon nanotubes are added, ultrasonically dispersed for 20-30 minutes, and then 0.01-0.1 parts of ammonium persulfate are added, and irradiated under ultraviolet light for 4-4.5 hours to perform a cross-linking reaction to obtain a modified sodium alginate / acrylic resin / silver-based carbon nanotube single network hydrogel precursor; Step 4: Soak 21 to 106 parts of modified sodium alginate / acrylic resin / silver-based carbon nanotube single network hydrogel precursor in 200 to 300 parts of 5% calcium chloride solution by mass for 2 to 3 hours to obtain a sodium alginate-based double-crosslinked antibacterial hydrogel flexible sensing material.
2. The method for preparing the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate according to claim 1, characterized in that: The carbon nanotubes in step 1 are single-walled carbon nanotubes with a purity of 95%, an outer wall diameter of 1 to 2 nm, and a length of 4 to 20 μm.
3. The method for preparing the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate according to claim 1, characterized in that: The mixed solution of sulfuric acid and nitric acid in step 1 is prepared by mixing a sulfuric acid solution with a mass fraction of 98% and a nitric acid solution with a mass fraction of 69.8% in a volume ratio of 2:
1.
4. The method for preparing the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate according to claim 1, characterized in that: The washing in step 1 is performed by washing with deionized water for 3 times.
5. The method for preparing the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate according to claim 1, characterized in that: The silver ammonia solution in step 1 is prepared by the following method: 30 mL of 2% silver nitrate solution is taken, and 2% dilute ammonia water is added dropwise thereto until the generated precipitate just disappears, thereby obtaining a clear and transparent solution, i.e., a 1.5% silver ammonia solution.
6. The method for preparing the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate according to claim 1, characterized in that: The vacuum drying temperature in step 1 and step 2 is 50-60°C.
7. The method for preparing the sodium alginate-based double-crosslinked antibacterial hydrogel flexible sensing material according to claim 1, characterized in that: The molecular weight of the sodium alginate in step 2 is 50,000 to 200,000, and the viscosity of the sodium alginate solution is 850 to 1000 mPa.s.
8. The method for preparing the double-crosslinked antibacterial hydrogel flexible sensing material based on sodium alginate according to claim 4, characterized in that: The purity of the sodium periodate, acrylic acid and N,N-methylenebisacrylamide is 99.5%.
9. A sodium alginate-based double-crosslinked antibacterial hydrogel flexible sensing material prepared by the method according to any one of claims 1 to 8.
10. Application of the sodium alginate-based double-crosslinked antibacterial hydrogel flexible sensing material according to claim 9 as a sensing material in flexible wearable devices, medical devices and human-computer interaction interfaces.